Pengaruh Aesthetic Labor Terhadap Positive Emotion di Saung Labuan Sundai Resort - Asya Dwi Yulia Putri; Nidia wulansari (STIKes Ibnu Sina Ajibarang, 2024)
This research is motivated by the problem of the influence of aesthetic labor on positive emotions at Saung Labuan Sundai Resort. This type of research is quantitative with a causal associative form. The study was conducted at Labuan Sundai Resort. The purpose of this study was to evaluate the influence of aesthetic labor on positive emotions at Saung Labuan Sundai Resort. The population in the study was 2,070 people taking a sample of 94 respondents. Data collection through a questionnaire with a Likert scale. Using descriptive analysis and interval class score classification through the SPSS program version 26.00 based on the results of the study, it is known that the overall indicator data with a result of 102.94 is categorized as very good. The aesthetic nature indicator with a result of 12.84 is categorized as very good. The aesthetic requirements indicator 21.69 is categorized as very good. The service encounter indicator 16.94 is categorized as very good. The happiness indicator 10.88 is categorized as sufficient. The satisfaction indicator 14.52 is categorized as sufficient. The love and affection indicator 10.75 is categorized as sufficient. The interest indicator 15.37 is categorized as good. The results of the study also showed a significant influence of aesthetic labor (X) on positive emotion (Y). The Adjusted R Square value of 0.778 indicates that these variables explain 77.8% of positive emotion, while the remaining 21.2% is influenced by other factors not examined in the study. Furthermore, the F value of 326.449 with a significance level of 0.000 <0.05 indicates a strong relationship between variables.s.